Transcatheter aortic valve implantation with a mechanically expandable prosthesis: a learning experience for permanent pacemaker implantation rate reduction - Jasmin Ortak; Giuseppe D’Ancona; Hüseyin Ince; Hüseyin U. Agma; Erdal Safak; Alper Öner; Stephan Kische (European Journal of Medical Research, 2018)
Abstract Background Permanent pacemaker implantation (PPMI) after transcatheter aortic valve implantation (TAVI) remains an issue open for criticism. Aim of this study is to investigate a strategy to reduce PPMI rate after TAVI in general and more specifically after implantation of the LOTUS® prosthesis. Methods Through our learning curve, we have developed a structured protocol to reduce PPMI rate. The protocol includes: shallow implantation depth within the native annulus, strict adherence to the international guidelines for PPMI, PPMI not earlier than 5 days after TAVI, and intravenous chronotropic and steroidal treatment (orciprenaline 0.6–1.7 mg/h i.v. and dexamethasone 25 mg/day i.v. for a maximum of 5 days) in case of acute onset of intraventricular and/or atrio-ventricular conduction disturbances after TAVI. Results The first 35 patients (group A) were managed as per routine in our early stage experience with the LOTUS valve. The PPMI reduction protocol was applied in the second phase on the last 31 patients (group B). The PPMI rate was reduced from 34.3% (12/35) to 9.7% (3/31) (p = 0.02). At logistic regression analysis being treated in the second phase of our experience (group B) had a protective effect against PPMI (p = 0.05; OR = 0.1; CI = 0.01–1.0). Prosthesis implantation depth was directly related to PPMI (p = 0.005; OR = 2.0; CI = 1.2–3.2). Receiver operating characteristic curve analysis confirmed that a LOTUS implantation depth > 4.8 mm was the cut-off to predict PPMI (AUC = 0.8; p = 0.003; CI = 0.6–0.9) with maximal sensitivity (78.6%) and specificity (73.2%). Conclusions PPMI rate after LOTUS can be reduced with experience by applying specific clinical and operative strategies.